Do constituency candidates matter in German Federal Elections? The personal vote as an interactive process. (September 2015) - Gschwend, Thomas; Zittel, Thomas
Abstract: What are the electoral consequences of constituency candidates' campaign strategies? This paper focuses on the German case to theoretically and empirically explore this question. Theoretically, it perceives personalization at the voter level as the result of an interactive process involving both candidates and voters. It argues that voters need to be asked and mobilized to personalize their votes in order of doing so. Empirically it draws from a novel set of data for the 2009 German Federal Elections including voters and candidate data. On the basis of this data set we are able to show that the campaign behavior of constituency candidates matters for the perceptions and behaviors of voters. Highlights: Article models and empirically explores the personal vote in Germany. Article shows that campaign styles of constituency campaigns matter. Personalized campaigns are able to win over non-partisan voters.